Pengembangan E-Modul Praktikum Berorientasi Chemoentrepreneurship (CEP) pada Materi Sifat Koligatif Larutan Kelas XII IPA SMA - Khairun Annisa; Maya Sari (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2021)
Various educational challenges today are building 21st century skills, including information and communication technology skills, critical thinking skills, and problem solving skills. This is in accordance with the implementation of the 2013 curriculum which is currently being implemented in Indonesia where students are required to improve their skills, especially skills during practicum so that the objectives of the learning process can be achieved. In the practicum, students will make observations, be trained to improve skills in practicum and use laboratory equipment. To achieve this, the teacher must use an attractive practicum guide by utilizing technology to be able to improve the skills and activeness of students during practicum. So that researchers are interested in using the E-Module practicum as a practicum guide which is almost displaced by the rapidly growing digital technology media. Through this practicum E-Module, it can increase the interest and activity of students during the practicum in understanding the material and work steps presented in the practicum E-Module. This practicum e-module is equipped with text combined with pictures and videos before students carry out practicums to support students' understanding before carrying out practicums. In order for the use of this practicum E-Module to run optimally, a learning approach is needed to add a more fun and interesting learning atmosphere so that the knowledge gained by students is not forgotten. Where this research uses R&D research to obtain products and test the effectiveness of product development. Through E-Mdoul chemoentrepreneurship-based practicum, currently researchers have qualitative and quantitative analysis data on product feasibility with a validator of 86.8% with valid criteria. While the E-Modul practicum test from the student response questionnaire is 98.3% with very practical criteria, while from the teacher's response questionnaire, the percentage is 98.9% from very practical criteria